A Reversible Redox Strategy for SWCNT‐Based Supercapacitors Using a High‐Performance Electrolyte1. Issue 2 (9th January 2013) - Yu, Haijun; Wu, Jihuai; Lin, Jianming; Fan, Leqing; Huang, Miaoliang; Lin, Youzhen; Li, Yan; Yu, Fuda; Qiu, Zhaoyuan
Abstract In order to achieve pesudocapacitive performance of single‐wall carbon nanotube (SWCNT) electrodes, a high‐efficient and reversible redox strategy utilizing a redox‐mediated electrolyte for SWCNT‐based supercapacitors is reported. In this novel redox‐mediated electrolyte, the single‐electrode specific capacitance of the supercapacitor is heightened four times, reaching C=162.66 F g−1 at 1 A g−1. The quick charge‐discharge ability of the supercapacitor is also enhanced, and the relaxation time is as low as 0.58 s. Furthermore, the supercapacitor shows an excellent cycling performance of 96.51 % retention after 4000 cycles. The remarkable results presented here illustrate that the redox strategy is a facile and straightforward approach to improve the performances of SWCNT electrodes.